(3LRA ajg hajGJ LeGYI ef GdeMOKjfs - (3GdMGLqj, GdCUHgGfj, CHh eSYhO, GHf CHj GdhaGA, YHO GdQMje Hf Ydj Hf CMeO, J (B566 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3bGd SeYJ GdTjN CHG eSYhO YHO GdQMje Hf CHj (B... (3CHj WGdH GdCUHgGfj jbhd PcQ haGI HYV eTGjNj hHYV CbQGfj QMege Gddg ; eGJ eMeO Hf YejQ Hf EHQGgje (B...s
(3BNQgG (B:s
... (3Jhaj CMeO Hf eMeO Hf GMeO Hf ehSi Hf eQOhjg Hf ahQj Hf ehSi Hf LYaQ Hf HcQ Hf SHW CHHj HcQ Hf eQOhjg aj SfI KeGf hJSYjf hCQHYeGFI HHhOQcGf bQjI ef bQi CUagGf (B.(3BNQgs
(3JHUQI GdYfhGf (B:s
(3QhGjI CHj eMeO YHO GdbGOQ Hf YHO Gddg GdQgGhjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\346s
(3GdCYdGe (B3\346s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs